(untitled) (Indonesian Journal of Education (INJOE), 2025)
In the era of globalisation and industrial revolution 4.0, innovation and digitalisation of education have become crucial factors in improving the global competitiveness of a nation. The research method used in this study is literature. The results show that effective integration of technology in the education system can create a learning environment that is more adaptive, personalised and relevant to the needs of the global market. Therefore, the importance of a holistic approach that considers aspects of accessibility, data security, and inclusion in the process of digitalisation of education